Model Pembelajaran Kuantum Teknik SNT dalam Pembelajaran Menulis Wacana Naratif - Burhanuddin, Burhanuddin (JPPI (Jurnal Pendidikan Islam Pendekatan Interdisipliner), 2017)
Quantum Learning Model Techniques SNT on Writing Narrative Discourse. The purpose of this study is (1) to describe the effectiveness of the technique SNT (Show Not Tell) on learning outcomes writing discourse narrative, (2) describe the difference skill write discourse narrative between students who used the technique SNT and students who use the type of TPS . This study is a quasi-experimental research design with pretest-posttest control group design. The population in this study as many as 22 people. The research instrument is a test instrument. Data were analyzed with descriptive statistics and inferential statistics. t test inferential analysis concluded that the ability to write short stories between classes using SNT technique is more effective than the model TPS mode. Hypothesis test results showed values of 0.000 Sig <0.05 (5%), which means that H1 is accepted or Techniques SNT (Show Not Tell) is more effective than the TPS mode for learning outcomes writing narrative discourse.